Comparing the Effectiveness of Dream Conceive and Analytical Imagery Approaches on Death Anxiety, Depression and Sleep Quality among Students - Reyhaneh Moghaddasi; Mohsen Golparvar; Hossein Hasan-Abadi (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: The dream conceives and analytical imagery approaches can affect many variables including mental disorders and mental health. The aim of this study was comparing the effectiveness of dream conceive and analytical imagery approaches on death depression, anxiety and sleep quality among students. Materials and Methods: The study was of semi-experimental design with pre-test, post-test and follow-up with control group. The statistical population consisted of students who were referred to counseling centers of Ferdowsi University of Mashhad in the winter of 2015, among whom 90 were selected and randomly divided into three equal groups. Therapeutic intervention was performed for two experimental groups, but no intervention was performed among the control group. The variables were measured before, after and three months after the intervention. Data were collected by Death Anxiety Inventory, Depression Scale and Sleep Quality Questionnaire. Data analysis was done by SPSS software version 16 using repeated measure design. Results: The mean (SD) age of participants was 31.6 (7.3) years. Death anxiety score in the pre-test of dream conceive group was decreased from 10.2 (2) to 6.1 (2.5) in post-test and 5.9 (2.6) in follow up, P<0.001. Death anxiety score in the analytic imagery group was reduced from 8.5 (2.7) in the pre-test to 4.9 (2.6) in the post-test and follow-up, but the mean (SD) of death anxiety scores of the control group in the pre-test, post-test and follow-up did not make any difference. The depression score in the pre-test group of dream conceive was decreased from 29.3 (10.6) to 11.5 (10) in the post-test and 9.2 (8.9) in the follow-up, P<0.001; depression score in the pre-test, the analytic imagery group was reduced from 25.8 (9.4) in the pre-test to 12.2 (8.7) in post-test and 11 (7.9) follow-up, but the mean (SD) depression scores in the control group did not differ in pre-test, post-test and follow-up. The sleep quality score in the pre-test of the dream conceive group decreased from 19.1 (8.1) to 9.6 (6.3) in the post-test and 7.1 (4) in the follow-up (P<0.001); the sleep disorder score in the pre-test of the analytic imagery group was reduced from 18.2 (9.4) in the pre-test to 9.4 (6.4) in post-test and 8.6 (6.2) in follow-up, but the mean (SD) of sleep quality in the control group did not differ in pre-test, post-test and follow-up. Comparing the two groups of dream conceive and analytical imagery approaches before, post-test and follow-up showed that there was no significant difference between the two groups in terms of death anxiety, depression and sleep quality. Conclusion: The study showed that both dream conceive therapy and analytical imagery reduced death anxiety, depression and sleep quality among students, but did not differ in the effectiveness of these two therapeutic approaches. DOI: http://doi.org/10.22037/ch.v7i1.24053